2018
DOI: 10.1002/cpe.5089
|View full text |Cite
|
Sign up to set email alerts
|

Optimized implementation of QC‐MDPC code‐based cryptography

Abstract: Summary This paper presents a new enhanced version of the QcBits key encapsulation mechanism, which is a constant‐time implementation of the Niederreiter cryptosystem using QC‐MDPC codes. In this version, we updated the implementation parameters to meet the 128‐bit quantum security level, replaced some of the core algorithms to avoid using slower instructions, vectorized the entire code using the AVX‐512 instruction set extension, and applied several other techniques to achieve a competitive performance level.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…The avx2 implementation follows the strategy above, where b is set to 256 to fit the size of YMM registers. Note that there is no general shift instruction for YMM registers, so the avx2 implementation follows [GAB19] to use AVX intrinsics to carry out the shift by s (0) positions.…”
Section: The Duplicated Form and The Barrel Shiftermentioning
confidence: 99%
See 2 more Smart Citations
“…The avx2 implementation follows the strategy above, where b is set to 256 to fit the size of YMM registers. Note that there is no general shift instruction for YMM registers, so the avx2 implementation follows [GAB19] to use AVX intrinsics to carry out the shift by s (0) positions.…”
Section: The Duplicated Form and The Barrel Shiftermentioning
confidence: 99%
“…In [GAB19], the authors suggested a simple way to improve the approach above. The idea is that, since adding b i only affects the first log 2 i + 1 bits of the counter, there is no need to update the remaining bits.…”
Section: Simple Algorithms For Computing the Hamming Weightmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, our general strategy and many of our constructions are familiar to cryptographers 18 . Some of these researchers have produced related optimizations using advanced SIMD instructions 19,20 .…”
Section: Related Workmentioning
confidence: 99%
“…The paper “ Optimized implementation of QC‐MDPC code‐based cryptography ” presents a new enhanced version of the QcBits key encapsulation mechanism (KEM), which is a constant time implementation of the Niederreiter cryptosystem using QC‐MDPC codes . The parallel solution uses vector instructions (AVX 512) and applies several other techniques to achieve a competitive performance level.…”
Section: Themes Of This Special Issuementioning
confidence: 99%